الأفعال المضارعة المعتلة و استعمالاتها في ديوان أبي فراس الحمداني (دراسة تحليلية صرفية نحويةوية) - ST. Fatimah T.E.K.U.A; Najmuddin; Andi Abdul Hamzah (Lentera Jurnal, 2025)
This research examines the use of imperfect verbs in poems related to pride in the Diwan of Abu Firas al-Hamdani from a morphological and syntactic perspective. morphology focuses on the structure of the verb and its conjugations, while syntax focuses on its inflection. The study aims to identify poems related to pride that use defective present tense verbs in the Diwan of Abu Firas al-Hamdani. This research is a qualitative study with a desk-based design. The data consists of defective present tense verbs, and the sources of the data are poems related to pride in the Diwan of Abu Firas al-Hamdani, while the data collection methodology is based on documentation. The researcher found that the total number of defective present tense verbs in the poems related to pride in the Diwan of Abu Firas al-Hamdani reached 521 verbs. The researcher hopes that this research will be a useful reference for deepening the understanding of defective present tense verbs in terms of morphology and syntax, especially in literary works such as poems related to pride. She also hopes that this research will contribute to enriching educational material that helps clarify the subject of defective present tense verbs so that students can gain a deeper understanding of it. She also hopes that this research will serve as a reference for future researchers to conduct further studies, especially in analyzing other linguistic aspects in the poetry of Abu Firas al-Hamdani or other Arabic literary works.